2005
DOI: 10.1038/sj.onc.1208534
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteolytic fragments from ErbB-2 that induce apoptosis

Abstract: The receptor tyrosine kinase ErbB-2 plays an important role in cell proliferation and differentiation as well as oncogenesis. We have found that ErbB-2 kinase domain fragmentation is important for the induction of apoptosis. Exogenous expression of peptides derived from the ErbB-2 kinase domain induces cells death with the hallmarks of apoptosis. In contrast, transfection of the ErbB-2 carboxy-terminal domain did not induce apoptosis. We have identified a 37-residue segment from the ErbB-2 kinase N-terminal lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…HER2 may also signal for apoptosis following degradation in hormone-sensitive prostate cancer cells (29). However, it is more likely that HER2 itself is not responsible for the mechanism underlying the effect were are observing, as 86% of the group of hormone-sensitive tumors that express high HER2 levels express high levels of two or more family members, and 46% have high expression levels of three or more family members.…”
Section: Discussionmentioning
confidence: 99%
“…HER2 may also signal for apoptosis following degradation in hormone-sensitive prostate cancer cells (29). However, it is more likely that HER2 itself is not responsible for the mechanism underlying the effect were are observing, as 86% of the group of hormone-sensitive tumors that express high HER2 levels express high levels of two or more family members, and 46% have high expression levels of three or more family members.…”
Section: Discussionmentioning
confidence: 99%
“…Some receptors already share some intriguing characteristics with DRs. For example, ErbB2, a receptor tyrosine kinase related to the EGF receptor family, can be cleaved by caspase, and the generated cytosolic fragment triggers apoptosis (Tikhomirov et al, 2005;Strohecker et al, 2008). Interestingly, this fragment contains a BH3-like domain related to the Bcl protein family involved in mitochondrial apoptosis.…”
Section: Future Members Of the Family?mentioning
confidence: 99%
“…[87][88][89][90] In addition, it has been demonstrated that full-length RET and ALK receptors display proapoptotic properties in the absence of their ligand and upon caspase processing. These receptors are then considered as potential dependence receptors that could also be involved in the regulation of apoptosis in a physiological context.…”
Section: Is Met On the Way To Dependence?mentioning
confidence: 99%